Pengaruh Kepemimpinan, Iklim Organisasi Dan Karakteristik Individu terhadap Kinerja Pegawai (Studi Kasus pada Kantor Kementerian Agama Kabupaten Mojokerto) - Mega Darmi Novita (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
This study aims to determine the effect of leadership, organizational climate and individual characteristics on employee performance at the Ministry of Religion Office in Mojokerto Regency, either partially or simultaneously. The research method used is a quantitative research method. The population and sample of this study were 80 employees at the Office of the Ministry of Religion in the Regency. The results of the research and discussion showed that leadership is not significance affecting the performance, while organizational climate, individual characteristics had an significance effect on employee performance. Leadership, organizational climate, individual characteristics had a significance effect on employee performance simoultantly. This means that if leadership, organizational climate and individual characteristics are improved, employee performance will increase.